Risk Factors for Time and Cost Overruns of Pipeline Projects in Saudi Arabia - Khalid Al-Gahtani; Maan Shafaay; Omar Ahmed; Marwan Alawshan; Naif Alsanabani; Saad Aljadhai (Advances in Civil Engineering)
Evaluating risks is crucial for the smooth execution of pipeline projects. In Saudi Arabia, pipeline building projects frequently experience delays and cost overruns. This study tries to identify these risk factors. Thus, risk factors were collected from the literature and presented to four experts to identify the 26 most common factors for pipeline construction in Saudi Arabia. The risk factors were then assessed using a questionnaire to measure the degree of impact of the 26 factors by 135 participants. Partial least square structure equation model (PLS-SEM) and relative importance index (RII) methods were utilized to rank the significant factors after performing the reliability and discriminant validity of the questionnaire data. The findings show that the top five factors based on PLS-SEM were discrepancy between implementation requirements and specifications, financial failure/bankruptcy, poor pipeline material quality, supplying invalid materials, and weak ability to identify and monitor the threats. The ranking of the factors using PLS-SEM is different in the RII method. This difference is due to applying the Cronbach’s α formula in the two methods. The PLS-SEM computes the coefficients of the groups, while the RII computes the coefficients for all factors. The study results can assist pipeline project managers in identifying and ranking risk variables to efficiently utilize the limited financial and human resources available for the risk management.